2012
DOI: 10.1074/jbc.m112.393140
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Promotes Survival of Renal Cancer Cells through Modulation of Apoptosis- and Autophagy-regulating Molecules

Abstract: Background:The cytoprotective enzyme HO-1 promotes tumor growth. Results: HO-1 down-regulated apoptosis-and autophagy-regulating proteins, and attenuated Rapamycin-and Sorafenibinduced apoptosis and autophagy in renal cancer cells. Conclusion: HO-1 protects cancer cells from chemotherapeutic drug-induced death by down-regulating apoptosis and autophagy. Significance: Inhibition of HO-1 augments efficiency of chemotherapeutic agents to kill cancer cells by promoting both apoptosis and autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 49 publications
4
79
0
Order By: Relevance
“…Currently, the role of autophagy in kidney disease remains controversial, as it is involved in both cell survival and death depending on different stimuli or cellular environment. 12,52 Our study provides in vitro and in vivo evidence that sustained HG resulted in defective autophagy in glomerulus and podocyte, which could be partially corrected by UDCA or 4-PBA treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, the role of autophagy in kidney disease remains controversial, as it is involved in both cell survival and death depending on different stimuli or cellular environment. 12,52 Our study provides in vitro and in vivo evidence that sustained HG resulted in defective autophagy in glomerulus and podocyte, which could be partially corrected by UDCA or 4-PBA treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The therapeutic efficacy of these drugs may be linked, at least in part, to HO-1 induction (reviewed in Dunn et al 2014). HO-1 expression in human renal cancer cells was induced by anti-renal cancer drugs rapamycin and sorafenib (Banerjee et al 2012). Intriguingly, a wide range of dietary antioxidants of plant origin such as curcumin, quercetin, tert-butylhydroquinone and caffeic acid phenethyl ester are HO-1 inducers so are catechin (in green tea), α-lipoic acid (in broccoli, spinach), resveratrol (in red wine, grapes), carnosol, sulphoraphane (cruciferous vegetable), coffee diterpenes cafestol and kahwoel (reviewed in Durante 2010).…”
Section: Ho-1 Induction By Therapeutic Drugs and Plant Antioxidantsmentioning
confidence: 99%
“…This demonstrates an indispensable role for HO-1 in the survival of the PT cells. Increased HO-1 expression in renal cancer cells promoted their survival and resistance to apoptosis (Banerjee et al 2012).…”
Section: Modulation Of Cadmium Toxicity By a Stress Response Mechanismmentioning
confidence: 99%
“…(Vinken et al, 2013;Banerjee et al, 2012;Zhu et al, 2014). Previous studies have shown that Lamellarin D is an alkaloid capable of inhibiting a variety of human tumors and has important significance in the treatment of tumors (Banerjee et al, 2012). By observing the effects of Lamellarin D on human leukemia K562 cells, this study found that Lamellarin D significantly inhibited tumor cell proliferation, induced apoptosis, and arrested cell cycle in G0/G1 phase.…”
Section: Discussionmentioning
confidence: 72%
“…Elucidation of the mechanisms of drug-mediated inhibition on tumor cell growth and proliferation has important significance for the treatment of tumors and the improvement of prognosis and there was a decreased mRNA and protein expression of tumor related gene such as CDK1, Survivin, Bcl-2 and so on. (Vinken et al, 2013;Banerjee et al, 2012;Zhu et al, 2014). Previous studies have shown that Lamellarin D is an alkaloid capable of inhibiting a variety of human tumors and has important significance in the treatment of tumors (Banerjee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%